STRAETGI DAKWAH KIAI ABDUL GHOFUR DALAM MAQOLAH AGOMO IKU NOTO APIKE KOYO OPO SEJE DESO SEJE CORO DI DESA SENDANGAGUNG KECAMATAN PACIRAN KABUPATEN LAMONGAN - Miftachul Ulum; Lathifatun Nisa’ (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2023)
In an effort to support the success of da'wah, a da'i is required to have wise strategies and have methods as a process in social institutions and awareness of the people. Strategy is a necessity to achieve a desired goal. In essence, strategy is a series of plans to achieve the desired goal. If it is related to the da'wah process, strategy has a very important role in the movement of da'wah activities, so that a da'i is required to have a strategy and method of building people's awareness. This research uses qualitative research with a type of approach through Ferdinan De Searsure's semiotic analysis. The flow of this research follows the concept of a da'wah approach, namely using a sociological da'wah approach and an anthropological da'wah approach.The results of this research indicate that the da'wah strategy in maqolah KH. Abdul Ghofur "Agomo Iku Noto Apik'e Koyo Opo Seje Deso Seje Coro" in Sendangagung Village proves that preaching must be adapted to the conditions of the local community. That what is good in village A is not necessarily good in village B.